Mathematic modeling of stress-deformed states of low jaw teeth while using combined removable splint-denture - Albert Ye.L.; Lysko O.I. (Medičnì Perspektivi)
The article presents the results of mathematical modeling and analysis of the stress-strain states of the lower incisors in the 1-st, 2-nd and 3-d degrees of inflammatory degenerative process in the periodontium; and while using combined splint-denture with continuous vestibular-oral clasp and polyoxymethylene framework. It is proved that reduction in height of interdental septa observed in periodontitis increases tooth mobility by 2.75 times in the first degree of the pathological process; by 6.75 times - in the second degree; and by 9.0 times – in the third degree (p<0.05 ). The pressure on the bone tissue transmitted through the teeth exceeds physiological one by 4.08; 5.04; 9.6 times for different degrees of severity of periodontal disease (p<0.05). In its turn, use of the proposed design of splint-denture reduces movement of the lower incisors in average up to 0.135±0.051 mm, that is equal to physiological parameters (p>0.05). At the same time, the stress, transmitted on the alveolar bone tissue is near the values of intact periodontium (p>0.05), 1.6±0.50 Mpa on average.